Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Etherification of biomass-derived glycerol to oxygenated fuel additives using dodecatungstophosphoric-silica-supported catalyst: characterization and kinetic studies - Magar, Subhash B.; Kapoor, Ashish; Jana, Sumit Kumar; Pal, Dan Bahadur; Rode, Chandrashekhar V. (Biomass Conversion and Biorefinery, 2023)
Commercial biodiesel production is becoming popular due to its sustainability and reduced greenhouse gas emissions in comparison to fossil fuels. Biodiesel production involves the co-generation of crude glycerol that is not directly viable. Valorization of glycerol is essential from techno-economic perspective to achieve goals of circular economy. In this study, the glycerol etherification was carried out using tert-butyl alcohol in presence of dodecatungstophosphoric/silica (DTP/SiO2) catalyst for production of tert-butyl glycerol ethers that can be used as fuel additives. A series of DTP/SiO2 catalysts were prepared with various compositions by impregnating heteropoly acids (HPA, H3PW12O40). The product analysis was performed to monitor mono-, di-, and tri-tert-butyl glycerol ethers. The kinetic studies were conducted based on Langmuir-Hinshelwood model. The rate constants were determined from experimental data by regression analysis. The catalysts were characterized by X-ray diffraction, SEM/EDX, and thermogravimetric analysis. Varying DTP loadings resulted in different catalytic activities. Activation energy (38.23 kJ/mol), activation enthalpy (25.94 kJ/mol), activation entropy (-163.8 J/mol/K), and Gibbs free energy of activation (88.67 kJ/mol) were attained for DTP/SiO2 (20%) catalyst that exhibited the best selectivity for di-tert-butyl glycerol ethers.
Keywords: Catalytic; etherification; fuel additives; Hinselwood; Impregnation; kinetics; Langmuir